2016
DOI: 10.1371/journal.pone.0156339
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Assessing and Identifying Workers’ Temperaments and Their Effects on Occupational Stress in the Workplace

Abstract: The relationship between temperaments and mental disorders has been reported in previous studies, but there has been little attention to temperaments in the occupational safety and health research. The aim of this study was to clarify the effects of temperaments on occupational stress among local government employees. The subjects were 145 Japanese daytime workers in local government. Temperaments were assessed by the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-Auto questionnaire (TEMPS-A). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
9
0
3
Order By: Relevance
“…15 Deguchi et al found a strong correlation between affective temperament and work stress perception in government administration workers. 24 Similar results were obtained by Polish authors who found a relationship between the depressive and anxiety dimensions and a higher risk of burnout syndrome and poorer health condition in nurses and civil servants. 16 Stress coping is defined as the process by which a person manages stress.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…15 Deguchi et al found a strong correlation between affective temperament and work stress perception in government administration workers. 24 Similar results were obtained by Polish authors who found a relationship between the depressive and anxiety dimensions and a higher risk of burnout syndrome and poorer health condition in nurses and civil servants. 16 Stress coping is defined as the process by which a person manages stress.…”
Section: Introductionsupporting
confidence: 80%
“…Hyperthymic temperament is associated with openness, ability to work under time and psychological pressure, and better functioning in stressful work situations. 16,24 As we predicted, the most common coping style was focused on task, which is connected with ability to constructive problem solving, and to reasonable planning as well. Managers obtained a higher score for hyperthymic temperament and a lower score for style focused on emotions than nonmanagers.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The TEMPS‐A examined relations between temperament, suicidal risk and bipolar disorders and found that suicide attempts or ideation and bipolar disorders are associated with anxious, cyclothymic, depressive and irritable temperaments (Mitsui et al, ; Toda et al, ; Vázquez, Gonda, Lolich, Tondo, & Baldessarini, ). In addition, other studies in non‐clinical fields investigated associations between nurses’ temperament and depressive symptoms and reported that a hyperthymic temperament played a role in protecting subjects from stress and depression and that depressive, cyclothymic, irritable and anxious temperaments were significantly associated with burnout, depression and over‐commitment (Deguchi et al, ; Jaracz et al, ; Kikuchi et al, ; Kikuchi, Nakaya, Ikeda, Takeda, & Nishi, ).…”
Section: Introductionmentioning
confidence: 99%